SNAPPER FISH PROCESSING AS A POTENTIAL RAW MATERIAL FOR FASHION JEWELRY - Susi Hartanto; Millen Valensie (Ide dan Dialog Desain Indonesia (Idealog), 2020)
Through numerous experiments (cleaning, drying, curve reduction, dyeing, folding, sealant), a set of methods is recommended as a better innovative method to process snapper fish scales to be used for fashion jewelry materials. The most effective method to clean fish scales is a combination of water and detergent. Colorants red yeast rice (red), turmeric (yellow), and Brilliant Blue FCF (blue) are most applicable colorants, producing a good range of colors. Soaking fishscales in pure vinegar is the best method to reduce curves. Folding fishscales should align with grain direction. All sequins embellishment techniques can be applied for fashion jewelry designs. These recommendations are seen more innovative and shows good characteristics of snapper fish scales (color, texture, transparency) compare to traditional process existing in the market. Keywords: fish, scale, snapper, fashion, jewelry